BUILDING MUTICULTURAL CHARACTER: THE INCLUSIVENESS OF CHARACTER EDUCATION IN ISLAMIC BOARDING SCHOOLS - Zamharil Zamharil; Yek Amin Aziz; Ahlan Ahlan (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
Islamic boarding schools, as traditional Islamic educational institutions in Indonesia, have an important role in character building of the younger generation. The background of this study is to explore how pesantren implement inclusive and multicultural educational characters amidst the increasing need for tolerance and diversity in society. This study aims to analyse the role of pesantren in teaching multicultural values as well as the challenges faced in the process. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, observations, and document analyses in several Islamic boarding schools that have implemented multicultural education. The focus of the research is on the application of multicultural values such as tolerance, justice, empathy, respect for equality, and equality in education and daily social interactions in pesantren. The results showed that the pesantren have integrated multicultural character education through various programs, such as interfaith dialogue, cross-cultural social activities, and a curriculum that includes knowledge about religious and cultural diversity. The main values taught in pesantren include tolerance, cooperation, mutual respect, and social justice. Santris are taught to appreciate differences and live in harmony with others, regardless of religious or cultural backgrounds. However, challenges such as resistance to change and the influence of globalisation remain obstacles. In conclusion, multicultural education in pesantren plays a significant role in forming a generation that is inclusive and has a strong character, ready to face poverty and global challenges.